Christianity in Hitler's ideology: the role of Jesus in national socialism - Nilsson, Mikael (Cambridge University Press, 2024)
"How did Hitler's personal religious beliefs shape the development of National Socialism? Through close analysis of primary sources, Mikael Nilsson challenges established narratives surrounding Hitler's relationship with Christianity, arguing that the figure of Jesus provided ideological inspiration for Hitler and the wider Nazi"